Preserving heritage of humanity: A systematic study of the pandemic impacts and countermeasures of the SMEs - Erlinda Nusron Yunus; Erni Ernawati; Endah Nuraini; Kartika Yuniarti (Administrative Sciences, 2023)
This study explores the most significant changes experienced by small- and medium-sized enterprises (SMEs) in Indonesia during the COVID-19 pandemic. It reveals the SMEs' strategies to survive and prosper amid the crisis. These actions are becoming increasingly invaluable and crucial for entrepreneurs in the heritage of humanity, such as Indonesian batik, who must stay in business to preserve national culture. This study conducts a systematic literature review of 42 relevant articles published between 2020 and the present and furthers the investigation using the Most Significant Change technique, involving in-depth interviews with 15 SME entrepreneurs. The results show that Indonesian batik SMEs struggled during the pandemic and experienced at least a 70% revenue reduction. Those who survived implemented retrenchment, persevering, and innovation strategies to achieve their short- and long-term goals. A temporary exit strategy was also applied in which business actors engaged in a different, more profitable business while awaiting normalcy. This study also found that true entrepreneurs' qualities, namely creativity and resilience, emerge in exceptionally difficult business situations.
Keywords: 350; COVID-19 pandemic; Indonesian batik; most significant changes; small and medium-sized enterprises; systematic literature review